Nutrición parenteral post-quirúrgica en un paciente canino sometido a corrección de ruptura vesical. Reporte de un caso - González D., María S.; Vélez, Catalina; Acevedo, Carlos M.; Ruiz S., Isabel (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary Parenteral nutrition (PN) consists of the application of intravenous nutrients to meet the nutritional requirements of a living being. It is used in patients who do not have the oral route enabled. This paper presents a report of a canine with ruptured bladder that was served at the "Centro de Veterinaria y Zootecnia de la Universidad CES (Medellín, Colombia) which will be corrected surgically placing a graft of a fragment of gastric tissue. NP was applied and that the animal did not provide food consumption by more than 5 days and had lost weight marked with delayed healing and therapy was needed nutritional support. As complication was presented edema venipuncture site on the second day of application for which the NP withdrew. The swelling was resolved quickly without any complication and with a noticeable improvement of the animal. The NP is an excellent tool for the clinical support of patients who do not have enabled the oral route because good nutrition allows for a better healing of tissues and better immune competence.